All‐trans‐retinoic acid ameliorates hepatic steatosis in mice by a novel transcriptional cascade. Issue 5 (26th March 2014) - Kim, Seong Chul; Kim, Chun‐Ki; Axe, David; Cook, Aaron; Lee, Mikang; Li, Tiangang; Smallwood, Nicole; Chiang, John Y.L.; Hardwick, James P.; Moore, David D.; Lee, Yoon Kwang
<x xml:space="preserve">Abstract</x> Mice deficient in small heterodimer partner (SHP) are protected from diet‐induced hepatic steatosis resulting from increased fatty acid oxidation and decreased lipogenesis. The decreased lipogenesis appears to be a direct consequence of very low expression of peroxisome proliferator‐activated receptor gamma 2 (PPAR‐γ2), a potent lipogenic transcription factor, in the SHP−/− liver. The current study focused on the identification of a SHP‐dependent regulatory cascade that controls PPAR‐γ2 gene expression, thereby regulating hepatic fat accumulation. Illumina BeadChip array (Illumina, Inc., San Diego, CA) and real‐time polymerase chain reaction were used to identify genes responsible for the linkage between SHP and PPAR‐γ2 using hepatic RNAs isolated from SHP−/− and SHP‐overexpressing mice. The initial efforts identify that hairy and enhancer of split 6 (Hes6), a novel transcriptional repressor, is an important mediator of the regulation of PPAR‐γ2 transcription by SHP. The Hes6 promoter is specifically activated by the retinoic acid receptor (RAR) in response to its natural agonist ligand, all‐trans retinoic acid (atRA), and is repressed by SHP. Hes6 subsequently represses hepatocyte nuclear factor 4 alpha (HNF‐4α)‐activated PPAR‐γ2 gene expression by direct inhibition of HNF‐4α transcriptional activity. Furthermore, we provide evidences that atRA treatment or adenovirus‐mediated RAR‐α overexpression significantly reduced hepatic fat accumulation in obese mouse models, as observed in earlier studies, and the beneficial effect is achieved by the proposed transcriptional cascade. Conclusions: Our study describes a novel transcriptional regulatory cascade controlling hepatic lipid metabolism that identifies retinoic acid signaling as a new therapeutic approach to nonalcoholic fatty liver diseases. (Hepatology 2014;59:1750–1760)